Frenchism in the Short Story ‘The Red-Headed League’ and ‘The Final Problem’ by Sir Arthur Conan Doyle - Bondan Eko Suratno (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Popular literary work, such as detective story, is an interesting phenomenon in literature since so many people like to read this kind of literary work. Popular literature in general has certain pattern called as formula. In this research, short stories written by Sir Arthur Conan Doyle in The Best of Sherlock Holmes become the research object. Two of them, ‘The Red-Headed League’ and ‘The Final Problems’ are chosen for showing uniqueness compared to the other eighteen titles with the massive use of French or other French-related terms. This phenomenon invites further research interest on what the author's intention and purpose in using French and other French-related things. The language aspect is included in the discussion field of Sociology of Literature, because language is basically created from social dynamic process. Thus, Alan Swingewood's Sociology of Literature approach which views literature as a mirror of age is considered to be appropriate for this research model. The analysis results of French construction and its related things through fictional characters in the short story show the author's expression who wants to describe the France atmosphere, the Britain-France relations, and their triumphs in the spheres of literature and economy. Keywords: popular literature, detective story, French, French-related things, sociology of literature